PEMETAAN DAN PEMERATAAN GURU BERDASARKAN BEBAN MENGAJAR GURU SMP NEGERI DI KECAMATAN TENAYAN RAYA PEKANBARU - Endang Kilatsih; Zulfan Saam; Sumarno Sumarno (Universitas Riau, 2019)
This study aims to determine the teachers state map, equity-based teacher teacher’s teaching load Junior High School in District Tenayan Raya Pekanbaru. Informants to be interviewed in this study were school principals, teachers, school supervisors and Head of the Education and Culture junior Pekanbaru. Instruments used in the form of interview, observation and documentation. Analysis of the data used to describe the data mapping and equal distribution of teachers by teachers’ teaching load Junior High School in District Tenayan Kingdom is a qualitative analysis. The results showed that the first, the implementation of the mapping program and the equal distribution of teachers has not gone well in school because teachers are still many shortcomings. Secondly, There are many teachers who have not been able to meet the mandatory teaching load at least 24 hours per week face to face. Third, the solution of barriers to the implementation of the program of mapping and generalization of junior high school teachers throughout the District Tenayan Raya Pekanbaru consists of several things of which to be transparent and accountable, carried out by the condition and where teachers live and give them the benefit of the mutation teacher to all the assembly of teachers in the environment of the District Tenayan Raya Pekanbaru. Key words: mapping, equal distribution of teachers, teaching loads